Copper Removal from Electroplating Wastewater by Coprecipitation of Copper-Based Supramolecular Materials: Preparation and Application Study - De-Kui Bai; Quan-Hong Ying; Ni Wang; Jin-Hui Lin (Journal of Chemistry)
This paper describes an experimental study for the removal of copper ions from electroplating wastewater. Different metal ions are added to the wastewater to remove copper ions by coprecipitation and the copper-based supramolecular materials with layered structures are obtained. It is found that the best results are obtained with the addition of –Mg2+–Al3+ mixture with ratio of 3 : 1, pH ≈ 10, and aging for 1 d at 60°C. With these conditions, the residual copper in the electroplating wastewater satisfies national emission standards and wastewater handling capacity of up to 30 mL can be achieved. The properties of the copper-based supramolecular materials prepared under these optimal conditions are characterized. The results show that the materials have a layered structure and good thermal and structural stability and achieve a saturated adsorption of iodide ions of 41.23 mg/g.